Review on Icephobicity of Materials Surface Enhanced by Interface Action Force - Lingfeng Zhao; Yizhou Shen; Jie Tao; Weilan Liu; Ting Wang; Senyun Liu (Advanced Materials Interfaces)
Abstract In response to the hazards of icing in the energy, transportation, and aerospace sectors, extensive research has been conducted on anti‐icing materials based on the solid‐liquid/ice interface theory, as well as reliable chemical and electro‐thermal de‐icing systems. However, there is an urgent need for modernizing anti‐icing systems to address diverse application scenarios. Gaining insights into the influence of interface action forces on water droplet behavior can proactively prevent detrimental icing occurrences. Nevertheless, under severe conditions where ice formation is inevitable, leveraging interface action forces to induce cracking and expansion of ice facilitates its rapid detachment despite potential challenges associated with complete removal. A comprehensive review elucidating the mechanisms through which interface action forces impact water/ice formations encompasses various approaches toward designing mechanically‐driven de‐icing systems.